Influence of red mud as a catalyst in the thermocatalytic reforming process - Onyishi, Hillary O.; Neidel, Johannes; Daschner, Robert; Apfelbacher, Andreas; Hornung, Andreas (Biofuels Bioproducts & Biorefining-Biofpr, 2024)
This work studies red mud, a residue from the processing of bauxite, as a support catalyst in the thermocatalytic reforming (TCR) process, using wood, digestate, and straw as case studies. Thermocatalytic reforming is a thermochemical process for the conversion of biomass into biofuels, combining intermediate pyrolysis and catalytic reforming and resulting in high-quality biofuels. The quantity and quality of the catalyst in the postreformer is vital as it influences the reactions taking place in it. Normally, nonreactive components of the char produced in the process act as the catalyst in the postreformer but adding a support catalyst may improve the products. In this work, red mud is introduced in the process by mixing it with the feedstock in a ratio of 1:3. The results, in comparison with normal TCR experiments on the same feedstock materials, show that the introduction of red mud into the process generally reduces the biochar yield and generally increases the biogas and product water yields, and the bio-oil yield remains constant. Its introduction also increases the hydrogen fraction of the gas and tends to reduce the nitrogen and sulfur content of the products, thus improving their quality. These observations are consistent across feedstock materials and postreformer temperatures. The results therefore suggest that red mud is a good support catalyst for increasing the gas yield, increasing the hydrogen fraction of the gas, and improving the quality of the products from the TCR process.
CRIS-Team Scopus Importer:2024-07-26
Keywords: biofuels; biomass; catalytic reforming; hydrogen; pyrolysis; red mud; thermochemical conversion